THE DIALECTIC OF LOVE IN EARLY PERSIAN SUFISM - Chittick, William C (Journal of Dharma, 2011)
In modern English, the word "mysticism" generally carries negative connotations, not least that of irrationality. I normally avoid it in my writings about the Islamic tradition, preferring instead the term Sufism, which at least suggests an appropriate cultural specificity and calls for a definition, I will not try to define it here; I instead, let me cite a description of mysticism by a specialist in Christianity.